1990
DOI: 10.1177/000348949009900502
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Semicircular Canal Occlusion for Intractable Benign Paroxysmal Positional Vertigo

Abstract: Benign paroxysmal positional vertigo (BPPV) is most often a self-limited disorder arising from the posterior semicircular canal of the undermost ear in the Hallpike position. Some individuals with this disorder have severe and protracted symptoms requiring more than expectant therapy. We describe two patients with intractable BPPV and profound sensorineural hearing loss in the affected ear treated by transmastoid posterior semicircular canal occlusion. Postoperatively, both were relieved of their BPPV and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
0
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(122 citation statements)
references
References 9 publications
1
117
0
4
Order By: Relevance
“…Among the care recommended, he suggested sleeping in a seated position or with 45 o elevation of the head for 48 hours after the maneuvers. Other authors 27,28 , who were stricter, recommended elevated head for 7 days after the maneuver, period in which sudden head movements and those that triggered dizziness would be avoided; not to sleep over the affected ear, and not to look up or down 29 . There were still others that instructed patients to wear a neck collar to prevent head movements 24,30,31 , a procedure not followed in our service owing to previous studies that suggested that neck collar and bone vibrator did not interfere in the outcomes of treatment 5,44 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the care recommended, he suggested sleeping in a seated position or with 45 o elevation of the head for 48 hours after the maneuvers. Other authors 27,28 , who were stricter, recommended elevated head for 7 days after the maneuver, period in which sudden head movements and those that triggered dizziness would be avoided; not to sleep over the affected ear, and not to look up or down 29 . There were still others that instructed patients to wear a neck collar to prevent head movements 24,30,31 , a procedure not followed in our service owing to previous studies that suggested that neck collar and bone vibrator did not interfere in the outcomes of treatment 5,44 .…”
Section: Resultsmentioning
confidence: 99%
“…The natural clinical course of BPPV is self-limited and takes from weeks to months, and it normally does not respond to antivertigo drugs [18][19][20] . Advocated treatments are various: maneuvers of canalith repositioningEpley maneuver is the most common one 21 , liberatory maneuvers, Semont 22 maneuver, vestibular habituation training [23][24][25] , and surgical treatments such as singular neurectomy or occlusion of posterior semicircular canal that are reserved to cases non-responsive to clinical treatment 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Пломбирование ЗПК получило более широкое рас-пространение, во-первых, благодаря отсутствию влияния на слуховую функцию, а во-вторых, из-за более простой техники исполнения, доступной для большинства отохи-рургов [42,43]. Кроме того, встречаются модификации этой техники с использованием аргонового или CO 2 -лазера [44].…”
Section: хирургическое лечение дппгunclassified
“…under experimental conditions that should prevent gravity-dependent endolymphatic convective currents (Sherer and Clarke, 1985;Stahle, 1990 ;Parnes and McClure, 1990).…”
Section: Introductionmentioning
confidence: 99%